2009
DOI: 10.17221/2502-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Elasticity of consumer demand on pork meat in the Slovak Republic

Abstract: consumers are the starting point of the final product market vertical line. Their demand is a crucial factor in the decisions about production -what to produce, how much, and what way. The aim of this paper is to provide the analysis of the elasticity of the consumer demand on pork, based on the influence of the change of the determinants influencing the demand on the consumer level of the vertical product line, and subsequent evaluation of the character and intensiveness of the consumer demand elasticities. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
0
10
0
2
Order By: Relevance
“…David (2009) discussed the problems of the commodity taxation on an example of the cigarettes taxation. Alternative approaches to the price elasticity estimation to our AiDS model were presented by Bielik and Sajbidorova (2009), hupkova et al (2009), zentkova and hoskova (2009 and Syrovatka (2006Syrovatka ( , 2007.…”
Section: Literature Reviewmentioning
confidence: 99%
“…David (2009) discussed the problems of the commodity taxation on an example of the cigarettes taxation. Alternative approaches to the price elasticity estimation to our AiDS model were presented by Bielik and Sajbidorova (2009), hupkova et al (2009), zentkova and hoskova (2009 and Syrovatka (2006Syrovatka ( , 2007.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are many research works and studies which showed that non-economic factors are becoming more important during the recent period in determining the consumers' purchasing decision (Bielik and Šajbidorová 2009;hupková et al 2009). The consumer (Solomon 2011;Šredl and Soukup 2011) want quality and value, however, these terms have slippery meanings that are hard for us to pin down.…”
mentioning
confidence: 99%
“…Comparable and consistent results indicate (Bielik, Šajbidorová, 2009) and in the conditions of Polish households (Gulbicka, Kwasek, 2006). Households have unmet nutritional needs due to their low purchasing power.…”
Section: Income Elasticity Of Food Expenditure and Its Expression Inmentioning
confidence: 67%